ANALISIS REPETISI DALAM BUKU KUMPULAN CERPEN RIAU POS PIPA AIR MATA - Hanifah Ikbar; Auzar Auzar; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated with the aim to discuss the types of repetition, the use of repetition,  and the meaning of repetition contained in the book collection of short stories Riau Pos Pipa Air Mata. The method used in this study is a qualitative method with data collection techniques in the form of documentation and recording techniques. Data analysis techniques in the form of identifying research data contained in a book collection of short stories Riau Pos Pipa Air Mata, grouping data that has been found according to the type of repetition This research is motivated with the aim to discuss the types of repetition, the use of repetition, and the meaning of repetition contained in the collection of short stories in the post Pipa Air Mata, classifying repetition data according to their use in the collection of Riau Post short stories Pipa Air Mata, grouping data repetition according to its meaning in a collection of short stories Riau Pos Pipa Air Mata. The results found that 115 data types of repetition, the first is epithetical repetition types there are 26 data, tautotes repetition there are 20 data, anaphoric repetitions have 29 data, epistrofa repetitions have 17 data, mesodiplosis repetitions have 16 data, and the last is repetition there are 20 data, anaphoric reps have 29 data, epistrofa repetition has 17 data, mesodiplosis repetition has 16 data, and the last is repetition epanalepsis there are 7 data. Next is the use of repetition of this study to describe the use in accordance with the use of the repetition itself. Furthermore, the meaning of repetition in this study is interpreted according to the meaning of the data that has been obtained. Key Words: Repetition, Types, Uses, Meaning Of Repetition